Water availability influences accumulation and allocation of nutrients and metals in short-rotation poplar plantation. (September 2018) - Tripathi, Abhishek Mani; Klem, Karel; Fischer, Milan; Orság, Matej; Trnka, Miroslav; Marek, Michal V.
Abstract: We analyzed the effect of manipulated water availability on an accumulation of nutrients and metals, their stoichiometry, and allocation to roots or leaves in a short rotation coppice (SRC) poplar plantation. The aim of this study was also to clarify how these changes are related to the effects of drought on growth parameters. This study was conducted in Domanínek, Czech Republic in an SRC poplar clone J-105 ( Populus nigra L. × P . Maximowiczii H.). This plantation was established as an uncoppiced (single stem) and later on converted into multi-stem (coppice). A rain-out shelter experiment (reduced throughfall) was established in the second year of coppice and the drought stress (DS) applied for 3 years. Water availability altered the accumulation and allocation of nutrients and metals in above and belowground biomass. Reduced water availability led, in particular, to the significantly lower accumulation of potassium (K) in both leaves and roots and a higher carbon (C) to potassium (K) ratio (C:K) in leaves. The significant decline of zinc (Zn) was also found in roots under reduced throughfall. Reduced water availability led to increased accumulation of cadmium (Cd) in leaves and decreased accumulation in roots. This resulted in significantly lower root:leaf ratio for Cd content. An opposite response was found for the allocation of copper (Cu). We also demonstrated that major changes in accumulation and allocation are associated with changes in growth. The results indicated that such knowledge may contribute to understanding the role of nutrient uptake and translocation in acclimation to DS and it may help in developing phytoextraction methods on contaminated soils. Highlights: Drought alters accumulation and allocation of elements in above and belowground biomass. Drought significantly changes cadmium (Cd) content in root:leaf ratio in poplar plantation. Reduced water availability led to the significantly lower accumulation of potassium (K) in both leaves and roots.